Paisagem urbana e experiência do pedestre: desenvolvimento e aplicação de ferramenta de leitura e avaliação crítica em percursos urbanos na região Centro Sul de Belo Horizonte - Henrique Vianna Lopes Teixeira (2020)
Although extensively studied by several authors in the field of urban design, the urban landscape and the experience of the built environment in contemporary cities were relegated to the background by overly functionalist urban planning practices in Brazil. It is important to highlight the interdisciplinary approach in this work. Recent studies in the field of neuroscience show the importance of the urban landscape for the experience of the built environment, and this for the health and well-being of the urban inhabitants. In this sense it is argued that the urban landscape should receive attention and importance equivalent to the functional and economic aspects in the practice of contemporary urban planning. In order to propose ways to fill this gap, an interdisciplinary tool was developed aiming to read and critically evaluate the urban landscape from the perspective of the pedestrian experience. This was applied to four urban routes in the south-central region of Belo Horizonte. As a result of the application, landscape transformation guidelines were drawn up to improve the pedestrian experience for each evaluated route. As a way to critically assess the applicability of the proposed guidelines, four properties were selected, one along each route, for the simulation of technical feasibility studies for new real estate projects. Through these simulations it was also possible to compare the proposed guidelines, the municipal legislation and the urbanistic parameters on each terrain. After analyzing these studies, it was verified the establishment of generic urban criteria and parameters for the four studied plots. It was also possible to verify the existence of conflicts between the current legislation and the guidelines proposed by this work for each terrain. The transformations allowed by the legislation, if carried out, may result in the homogenization of the townscape in the area, in the suppression of the unique characteristics of each stretch and in the fragmentation of the landscape in the studied streets. Ultimately, it is concluded that the municipal legislation does not include pedestrian experience or landscape planning in its guidelines, standards and parameters for new construction and devempment.